HPR1000 pressurizer degassing system design and analysis - Cui, Huaiming; Cai, Zhiyun (Frontiers in Energy Research, 2024)
In the Hualong-1 Unit (HPR1000), the hydrogen (H2) concentration should be reduced to 15 mL (STP)/kg 24 h before reactor shutdown when the reactor vessel is scheduled to be opened. The traditional degassing method, i.e., letting down the reactor coolant through a chemical and volume control system, will take longer, and its operation is more complicated. To shorten the degassing time and simplify the operation, this paper proposes a pressurizer degassing system design for HPR1000 by applying the pressurizer as thermal degassing equipment. Then, the degassing system optimization analysis is carried out under a full range of steady operating conditions during shutdown, and the optimal size of the flow-limiting orifice plate is obtained. Meanwhile, in order to verify the transient characteristic during the degassing process to ensure operating safety, a dedicated transient degassing program based on an improved non-equilibrium multi-region pressurizer model and a transient degassing model is used to carry out a transient simulation analysis of this process. The transient simulation results show that, under bounding conditions of hot–zero-power operation, during the degassing process, the pressure of the pressurizer decreases by a maximum of 0.038 MPa and the water level increases by 0.016 m above the normal level. As can be seen, both the pressure and water level are within the normal operation band and shall not initiate any safety signal. Meanwhile, the entire transient process lasts approximately 24 min and then enters a stable degassing period. It takes approximately 5.2 h to remove the gas dissolved in the reactor coolant from 35 mL (STP)/kg to 15 mL (STP)/kg. The analysis shows that the pressurizer degassing system designed for HPR1000 is safe, effective, and reliable.